Preserving wintering frugivorous birds in agro‐ecosystems under land use change: Lessons from intensive and super‐intensive olive orchards. Issue 12 (3rd October 2021) - Morgado, Rui; Pedroso, Rui; Porto, Miguel; Herrera, José M.; Rego, Francisco; Moreira, Francisco; Beja, Pedro
Abstract: Fleshy fruit production is becoming more intensive worldwide, but how this affects frugivorous birds is poorly known. In the Mediterranean region, intensive and super‐intensive olive orchards are fast expanding, potentially affecting millions of wintering songbirds. Here, we test the idea that intensification may benefit frugivorous birds, at least locally, due to increased fruit availability, while negatively affecting the wider wintering bird community due to intensive management, structural simplification and landscape homogenisation. We estimated olive abundance and surveyed birds in early, mid‐ and late winter, at traditional, intensive and super‐intensive orchards in southern Portugal. We used Hierarchical Modelling of Species Communities to relate species richness, prevalence and abundance to management intensity, winter period, olive availability and landscape context, and evaluated the role of frugivory in modulating observed responses. Olive availability was much higher throughout the winter in more intensive than in traditional orchards, both in trees and on the ground. Frugivorous bird abundance was higher in more intensive orchards, and the most abundant frugivorous species (blackcap, song thrush, robin) were positively affected by olive availability and/or increasing landscape cover by olive orchards, while intensification level had relatively minor effects after accounting for other variables. Non‐frugivorous richness and abundance were higher in traditional orchards, and many non‐frugivorous species had lower prevalence in more intensive orchards or were negatively affected by landscapes dominated by olive cultivation. Synthesis and applications . While negatively affecting the wider bird community, our results suggest that olive farming intensification can contribute to sustaining large numbers of frugivorous birds in the Mediterranean region. As frugivorous birds are not seen as damaging by olive farmers, there is an opportunity to promote their conservation in intensive and super‐intensive orchards, which requires management to increase habitat heterogeneity, and to reduce risks such as mortality associated with mechanical harvest and contamination with pesticide residues. Overall, we recommend that efforts to manage farmland biodiversity should consider the impacts and conservation opportunities of fruit crop intensification. Abstract : While negatively affecting the wider bird community, our results suggest that olive farming intensification can contribute to sustaining large numbers of frugivorous birds in the Mediterranean region. As frugivorous birds are not seen as damaging by olive farmers, there is an opportunity to promote their conservation in intensive and super‐intensive orchards, which requires management to increase habitat heterogeneity, and to reduce risks such as mortality associated with mechanical harvest and contamination with pesticide residues. Overall, we recommend that efforts to manage farmland biodiversity should consider the impacts and conservation opportunities of fruit crop intensification.